2021
DOI: 10.1007/978-3-030-85914-5_12
|View full text |Cite
|
Sign up to set email alerts
|

A Formal Skill Model Facilitating the Design and Operation of Flexible Assembly Workstations

Abstract: In the Industry 4.0 area, there is an increasing demand for highly customized products in small batch sizes. Final assembly operations are frequently targeted to embed flexibility and compensate for the growing manufacturing uncertainties. Therefore, an adequately designed and operated flexible assembly workstation is crucial. Converting the flexibility needs into design and operational decisions requires versatile formal models delivering generic descriptions of needs and capacities. Skills form the central c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Especially on the meaning and use of the term 'skill' versus 'capability', multiple viewpoints exist. Previous work showed that, as the here-introduced model is broad and de facto spans both terms, the term 'skill' is a logical choice for our research (Van De Ginste et al (2021)). The State-Of-The-Art (SOTA) in skill-based modelling is discussed in section 2.1.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially on the meaning and use of the term 'skill' versus 'capability', multiple viewpoints exist. Previous work showed that, as the here-introduced model is broad and de facto spans both terms, the term 'skill' is a logical choice for our research (Van De Ginste et al (2021)). The State-Of-The-Art (SOTA) in skill-based modelling is discussed in section 2.1.…”
Section: Related Workmentioning
confidence: 99%
“…(2) During the kick-off the modelling challenges were discussed (section 2.2) and the model requirements were further clarified (section 3.2). Together with researchers in multiple fields from the strategic centre for the manufacturing industry in Flanders, a series of workshops led to a first version of the formal skill model (Van De Ginste et al (2021)). (3) Next, refinements of this model were made specifically for assembly.…”
Section: Development Processmentioning
confidence: 99%